A SYSTEMATIC REVIEW OF SUSTAINABLE SPORTWEAR CONSUMPTION IN INDONESIA : TREND AND FUTURE DIRECTION - Widyanti, Nurul; Rusfian, Effy Zalfiana (Ridwan Institute, 2024)
In recent years, sustainability has become an increasingly prominent focus in the global sportswear industry, driven by growing environmental awareness and consumer preferences. However, little research has specifically addressed the trends and drivers of sustainable sportswear consumption in Indonesia, a country marked by its unique cultural, economic, and environmental landscape. This systematic review aims to synthesize current knowledge on sustainable sportswear consumption trends in Indonesia, examining factors influencing consumer behavior, key challenges, and opportunities for future development in this sector. The researchers conducted a comprehensive literature review using primary databases (e.g., Scopus, Web of Science) to identify studies that explore the environmental, social, and economic dimensions of sustainable sportswear in Indonesia. Our analysis reveals that Indonesian consumers are gradually shifting toward eco-friendly products, yet barriers such as limited awareness, higher costs, and low market penetration of sustainable brands persist. Additionally, Indonesian culture and socio-economic diversity present unique challenges and opportunities for promoting sustainable sportswear, especially among young consumers and urban populations. The review identifies a clear trend toward environmentally-conscious consumption patterns, albeit at a slower pace compared to Western countries. Future research should focus on developing targeted marketing strategies that resonate with local values, affordability, and awareness campaigns that emphasize the benefits of sustainable consumption. The findings of this review highlight the potential for Indonesia to grow as a sustainable sportswear market, provided that efforts are made to align industry practices with consumer expectations and environmental priorities.